Effect of Single and Mixed Inoculum on Biogas Yield During Dry Anaerobic Digestion of Organic Municipal Solid Waste (Chemical Engineering Research Bulletin, 2021)
Organic municipal solid waste (OMSW) - a potential energy source - is creating serious environmental hazards across Bangladesh, but it can be digested for biogas production to meet the ever-increasing energy demand of the country. The present study applied the dry anaerobic digestion (DAD) process for biogas production from OMSW with inoculum cow manure (CM) and anaerobic sludge (AS) in single and mixed modes. The performance of the DAD process was evaluated in batch digesters with a multilayer inoculum flow pattern maintained at the constant mesophilic condition of 37 °C. Firstly, CM and AS were studied individually, and later on, both of them were used together in different ratios (AS:CM = 1:1, 1:2, 1:3, and 2:1) to maximize the biogas yield from the DAD process. CM alone produced a total of 2.91 ml biogas/ g of biomass over 35 days of DAD while this yield was increased to 3.19 ml/g for mixed inoculum at the ratio of 1:3. These results imply that mixed-mode inoculums would be a promising option in the DAD process for biogas production which will reduce both the energy scarcity and the burden of municipal solid waste (MSW) management.Chemical Engineering Research Bulletin 21(2020) 77-81